2020
DOI: 10.1186/s12944-020-01249-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel LPL nonsense variant and further insights into the complex etiology and expression of hypertriglyceridemia-induced acute pancreatitis

Abstract: Background: Hypertriglyceridemia (HTG) is a leading cause of acute pancreatitis. HTG can be caused by either primary (genetic) or secondary etiological factors, and there is increasing appreciation of the interplay between the two kinds of factors in causing severe HTG. Objectives: The main aim of this study was to identify the genetic basis of hypertriglyceridemia-induced acute pancreatitis (HTG-AP) in a Chinese family with three affected members (the proband, his mother and older sister). Methods: The entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…In addition, hypertriglyceridemia‐associated AP accounts for approximately 50% of the study subjects, significantly different from cohorts reported in other areas of the world 29,30 . The increase in hypertriglyceridemia‐induced AP in the Chinese population might be attributed to dramatic changes in dietary habits 31 and genetic factors 32 . Although the performance of mPASS‐4 in predicting IPN did not change after involving the etiologies as a confounder, the distinct etiological distribution may weaken the generalizability of our observed results.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In addition, hypertriglyceridemia‐associated AP accounts for approximately 50% of the study subjects, significantly different from cohorts reported in other areas of the world 29,30 . The increase in hypertriglyceridemia‐induced AP in the Chinese population might be attributed to dramatic changes in dietary habits 31 and genetic factors 32 . Although the performance of mPASS‐4 in predicting IPN did not change after involving the etiologies as a confounder, the distinct etiological distribution may weaken the generalizability of our observed results.…”
Section: Discussioncontrasting
confidence: 59%
“… 29 , 30 The increase in hypertriglyceridemia‐induced AP in the Chinese population might be attributed to dramatic changes in dietary habits 31 and genetic factors. 32 Although the performance of mPASS‐4 in predicting IPN did not change after involving the etiologies as a confounder, the distinct etiological distribution may weaken the generalizability of our observed results.…”
Section: Discussionmentioning
confidence: 63%
“…Last, nearly 50% of the study patients had hypertriglyceridemia as etiology, significantly higher than results from an international registry [ 47 ]. The increase of hypertriglyceridemia-induced AP in Chinese cohorts might be attributed to changes in dietary habits [ 48 ] and genetic factors [ 49 ]. Although the effect of Tα1 did not vary across patients caused by hypertriglyceridemia or other etiologies, the distinct etiological distribution leaves the generalisability of the observed results in doubt.…”
Section: Discussionmentioning
confidence: 99%
“…LPL mass was determined using a human LPL Elisa kit (TSZ Biological Trade Co., Ltd., San Francisco, CA, United States) in accordance with the manufacturer’s instructions. To measure LPL activity, plasma total lipase activity and hepatic lipase activity were first determined by a LPL-mediated lipolysis reaction; this was performed by means of a free fatty acid (FFA) release assay kit [Wako kit# NEFA-HR(2), Japan], using TG-rich plasma from GPIHBP1 -deficient ( GPIHBP1 –/– ) mice as the lipolytic substrate ( Li et al, 2020 ; Shi et al, 2020 ). It should be noted that, for the hepatic lipase activity assay, the sample was pretreated with 1 M NaCl and incubated for 60 min at 4°C in order to inactivate LPL.…”
Section: Methodsmentioning
confidence: 99%
“…The wild-type LPL cDNA expression vector has been previously described ( Li et al, 2020 ; Shi et al, 2020 ) and was used here to generate the mutant [c.756T > G (p.Ile252Met)] expression vector by site-directed mutagenesis. The mutated site was verified by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%